Standarization of business model for standard data modeling - Reyna Monteverde, Tino Eduardo (2016)
This paper presents a new approach for determining the functional business model required for the data model of the future automated system. The scope of this new scheme covers the typical business that requires information systems for business decision making. Patterns of functional areas of any enterprise are analyzed, reaching present standard schemes for each. These patterns are displayed and properly supported. Information Systems for life undergo a series of adjustments via maintenance. These changes generate many costs in time and money. The strategy to avoid this situation is to build on standard business models, which can be customized according to parameters in particular. In order to find the standard business model there are four basic functions Macro universally must be present in all areas of business. These macro functions are presented and detailed. To reach this scheme shows that the service provided by all areas that form the company are type Service Products and therefore must comply holistically with the product life-cycle management (four stages of the cycle). The models are presented both graphically and analytically. They are determined iOn requirements, essential for the analysis stage of the Information Systems based on this standard model business.